Determinants of Use of the Care Information Exchange Portal: Cross-sectional Study - Ana Luisa Neves; Katelyn R Smalley; Lisa Freise; Paul Harrison; Ara Darzi; Erik K Mayer (JMIR Publications, 2021)
BackgroundSharing electronic health records with patients has been shown to improve patient safety and quality of care. Patient portals represent a convenient tool to enhance patient access to their own health care data. However, the success of portals will only be possible through sustained adoption by its end users: the patients. A better understanding of the characteristics of users and nonusers is critical for understanding which groups remain excluded from using such tools. ObjectiveThis study aims to identify the determinants of the use of the Care Information Exchange, a shared patient portal program in the United Kingdom. MethodsA cross-sectional study was conducted using a web-based questionnaire. Information collected included age, gender, ethnicity, educational level, health status, postcode, and digital literacy. Registered individuals were defined as having had an account created in the portal, independent of their actual use of the platform; users were defined as having ever used the portal. Multivariate logistic regression was used to model the probability of being a user. Statistical analysis was performed in R and Tableau was used to create maps of the proportion of Care Information Exchange users by postcode area. ResultsA total of 1083 participants replied to the survey (186% of the estimated minimum target sample). The proportion of users was 61.58% (667/1083). Among these, most (385/667, 57.7%) used the portal at least once a month. To characterize the system's users and nonusers, we performed a subanalysis of the sample, including only participants who had provided at least information regarding gender and age. The subanalysis included 650 individuals (389/650, 59.8% women; 551/650, 84.8% >40 years). Most participants were White (498/650, 76.6%) and resided in London (420/650, 64.6%). Individuals with a higher educational degree (undergraduate and professional, or postgraduate and higher) had higher odds of being a portal user (adjusted odds ratio [OR] 1.58, 95% CI 1.04-2.39 and OR 2.38, 95% CI 1.42-4.02, respectively) compared with those with a secondary degree or below. Higher digital literacy scores (≥30) were associated with higher odds of being a user (adjusted OR 2.96, 95% CI 2.02-4.35). Those with a good overall health status had lower odds of being a user (adjusted OR 0.58, 95% CI 0.37-0.91). ConclusionsThis work adds to the growing body of evidence highlighting the importance of educational aspects (educational level and digital literacy) in the adoption of patient portals. Further research should not only describe but also systematically address these inequalities through patient-centered interventions aimed at reducing the digital divide. Health care providers and policy makers must partner in investing and delivering strategic programs that improve access to technology and digital literacy in an effort to improve digital inclusion and reduce inequities in the delivery of care.